Revisiting methicillin-resistant Staphylococcus aureus infections - Abdelkarim Waness (Journal of Global Infectious Diseases, 2010)
Within less than 50 years, methicillin-resistant Staphylococcus aureus (MRSA) made a tremendous impact worldwide. It is not limited to medical facilities and healthcare institutions anymore. Indeed since two decades, cases of MRSA infections arising from the community among apparently healthy individuals are increasing. In this paper, I will present a case of community-associated MRSA sepsis followed by a comprehensive review about the history, pathogenesis, epidemiology, clinical presentations, diagnostic modalities, therapeutic options, contributing factors, growing cost and other pertinent elements of this newly evolving epidemic of MRSA infections.